Contraceptive nonuse among women in Uganda: a comparative assessment of predictors across regions - Jude Otim (BMC, 2020)
Abstract Background Contraceptive nonuse has diverse effects on women, such as unintended pregnancies and births that result in high fertility and poor maternal health outcomes. In Uganda, knowledge on contraceptive use is high, amidst undesirably high contraceptive nonuse and scarce literature on predictors of contraceptive nonuse across regions. This study assessed factors associated with contraceptive nonuse among women of reproductive age across regions in Uganda. Method This study used data from a cross-sectional 2016 Uganda demographic and heath survey that had 18,506 women of reproductive age. The relationship between contraceptive nonuse and socio-economic and demographic factors across regions were assessed using a binary multivariable logistic regression model. Results In Uganda, contraceptive nonuse is estimated at 40%. Northern region (55%) had the highest prevalence of contraceptive nonuse compared to Central region (35%) with the lowest. Across regions, wealth index, number of living children, educational level, and children born in the last 5 years prior to the demographic survey differently predicted contraceptive nonuse. Conversely, age, religion, age at first marriage, sexual autonomy, age at first birth, desire for children, listening to radio, and employment status were only predictors of contraceptive nonuse in particular regions amidst variations. Residence, perception of distance to health facility, watching television, and reading newspapers or magazines did not predict contraceptive nonuse. Conclusions The study findings propose the need to appreciate regional-variations in effect of contraceptive nonuse predictors and therefore, efforts should be directed towards addressing regional-variations so as to attain high contraceptive usage across regions, and thus reduce on unwanted pregnancies and births.